The Effect of Preoperative Oral Carbohydrate Loading on Stress Response in Patients Undergoing Major or Minor Surgery - BEKİROĞLU, GÜLNAZ NURAL; ÇORMAN DİNÇER, PELİN (ORTADOGU AD PRES & PUBL CO, 2011)
Objective: The aim was to investigate the effects of preoperative oral carbohydrate administration on hunger, thirst or dryness of the mouth, nausea-vomiting, the onset time of bowel movements, discharge time and the stress response of the patients undergoing major or minor surgery. Material and Methods: Ninety patients were divided into two groups as major and minor surgery. Each group was divided into three subgroups as study, placebo and control. The study group drank oral carbohydrate solution and placebo group drank water, 800 ml the night before and 400 ml two hours before surgery. Patients in the control group did not drink any fluid. The severity of thirst, hunger and dryness in the mouth, fatigue and nausea-vomiting were assessed. Plasma cortisone, insulin and glucose levels were measured. The onset of bowel movements and discharge time were recorded. Results: The number of patients with hunger, thirst or dryness in the mouth were significantly smaller in study and placebo groups compared to controls (p<0.05). Postoperative nausea-vomiting was less in the study group (p<0.01). After both major and minor surgery, blood glucose levels in study group returned to preoperative values at 24th hour whereas they remained high in placebo and control groups (p<0.01). Insulin values increased at postoperative sixth hour in study group, and at postoperative 24th hour in control and placebo groups (p<0.01). The onset of bowel movements was earlier in control group after minor surgery (p<0.01). Conclusion: Administration of a carbohydrate-rich fluid or water before the surgery reduces the severity of thirst, hunger and dryness in the mouth. Carbohydrate rich fluid decreases postoperative nausea-vomiting and insulin resistance. It fastens the onset of bowel movements after minor surgery.
Keywords: Preoperative care; fasting; stress, physiological; POSTOPERATIVE INSULIN-RESISTANCE; RANDOMIZED CONTROLLED-TRIAL; GASTRIC FLUID VOLUME; ELECTIVE SURGERY; LAPAROSCOPIC CHOLECYSTECTOMY; ABDOMINAL-SURGERY; CLINICAL-TRIAL; NUTRITION; OPERATION; DRINK